Large de novo DNA deletion in a patient with sporadic neurofibromatosis 1, mental retardation, and dysmorphism. Issue 10 (October 1992) - Kayes, L M; Riccardi, V M; Burke, W; Bennett, R L; Stephens, K
Abstract : A mildly dysmorphic, mentally retarded male with neurofibromatosis 1 (NF1) was found to have a de novo deletion of chromosome 17. The deletion occurred on the paternally derived chromosome 17 as shown by the absence of a D17S73 paternal allele. Densitometric analysis indicated that, in addition to the D17S73 locus, the patient has only one copy of four other adjacent loci. The deletion involved the loci D17S120, NF1, D17S57, D17S115, and D17S73 and was estimated to encompass more than 380 kb of DNA. The deletion of the entire paternal NF1 allele argues strongly that this disorder is not caused by the action of an abnormal NF1 protein. The extent of the deletion suggests that the mental retardation and dysmorphism of this patient may result from a deletion involving both the NF1 gene and contiguous genetic material.